Pendekatan Pembelajaran Analisis Nilai Pada Mata Kuliah Konsep Dasar Pendidikan Kewarganegaraan - Apri Irianto (Universitas PGRI Adi Buana Surabaya, 2020)
This type of research is qualitative by describing and describing the conditions of learning using the value analysis approach. The study was conducted from September to October 2019, implemented in 8 times the lecture. Related to student activities in the lecture using the analysis approach of the value obtained the data that the learning using the value approach applied in the class 2019-G Students PGSD PGRI Adi Buana University can foster student inactivity, confidence, writing skills, and concept comprehension. With the value approach applied by researchers, it can make students dare to perform and convey ideas that are in mind.